1972
DOI: 10.1037/h0033232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interpreter credibility and discrepancy level of results on responses to test results.

Abstract: Subjects were given artificial psychological test results that were discrepant in either positive or negative directions with their self-reports on the traits purportedly measured. Test results were given by a counselor identified as either a PhD or a counseling practicum student. Amount of discrepancy between test results and self-report significantly affected the amount of change in self-report of subjects in both positive and negative feedback conditions. Professional level of the interpreter affected chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…1963;Bergin, 1962). A number of analogue studies have shown therapist expertness to be positively correlated with the patient's choice of therapist 11 (Corrigan, 1978), levels of rated attraction and trustworthiness (Greenberg, 1969;McKee & Smouse, 1983), information re~all (Guttman & Haase, 1972), attitudinal change (Binderman, Fretz, Scott & Abrams, 1972;Bergin, 1962) and to both self reported and actual behavior change (Dell, 1973;Hoffman & Spencer, 1977). In one of a few naturalistic long term treatment studies, Beutler, et ale (1975) found that patients post hoc perceptions of therapist credibility were significantly and positively related to patient improvement.…”
Section: Credibilitymentioning
confidence: 99%
“…1963;Bergin, 1962). A number of analogue studies have shown therapist expertness to be positively correlated with the patient's choice of therapist 11 (Corrigan, 1978), levels of rated attraction and trustworthiness (Greenberg, 1969;McKee & Smouse, 1983), information re~all (Guttman & Haase, 1972), attitudinal change (Binderman, Fretz, Scott & Abrams, 1972;Bergin, 1962) and to both self reported and actual behavior change (Dell, 1973;Hoffman & Spencer, 1977). In one of a few naturalistic long term treatment studies, Beutler, et ale (1975) found that patients post hoc perceptions of therapist credibility were significantly and positively related to patient improvement.…”
Section: Credibilitymentioning
confidence: 99%
“…Specifically, we found that the client's perception of therapist status and the client's attitude toward therapy were significant moderators of his or her acceptance of self-inconsistent feedback. These findings further supported the role of source factors, such as status (e.g., Binderman et al, 1972;Hovland & Weiss, 1952), and attitudinal factors, such as discrepancy from one's own views (e.g., Sherif & Sherif, 1967), in determining message acceptance.…”
Section: Discussionmentioning
confidence: 57%
“…Highstatus therapists are a case in point of expert power (French & Raven, 1959), indicating the possibility that clients would perceive them as more credible and competent than low-status therapists. Supporting this possibility, Binderman, Fretz, Scott, and Abrams (1972) found that high-credibility therapists (i.e., counselors with doctorates) were able to evoke greater acceptance of selfinconsistent personality feedback from participants than low-credibility therapists (i.e., counseling practicum students).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…External Factors. External factors of counselors that have shown to be connected with client dropout from counseling include the following factors: interruption of the counseling relationship such as counselor vacations or absences (Straker et al, 1967); counselor display of awards and diplomas (Siegel & Sell, 1978); counselor credentials and prestigious reputations (Binderman, Fretz, Scott, & Abrams, 1972;Friedenberg & Gillis, 1977;Hartley, 1969); counselor attire (e.g., moderately formal was most positively perceived) (Rain, 1973); and counselors' room furnishings (Kerr, 1982;Miller, 1981).…”
Section: Counselor Qualitiesmentioning
confidence: 99%